PERAN PENDIDIKAN AGAMA ISLAM DALAM MENUMBUHKAN KARAKTER ANTI KORUPSI - Sofian, Amrin (Jurnal Pendidikan Guru, 2017)
Multi-dimensional problems of the crisis concerning the foundations of a very demanding their efforts to solve urgent. Problematic concerning the order of values in society one of them is the problem of corruption that never ended. Because the more acute the problem, some people consider corruption in Indonesia has become a culture and even a virus epidemic which must be fought together. This article aims to reinforce the return of Islamic education in fostering anti-corruption code. Because in Islam it is clear that corruption (such as bribery, kickbacks, extortion, graft and other forms of corruption) are accursed act, haraam and got serious threat doomsday at the end of the perpetrator. Corruption, impact in many peoples lives, whether economic, political, social and cultural. Generally, corruption reduce the quality of public services. As a victim of corruption, the society that most felt the impact of corruption. Role of Islamic Education can be applied in the School/Madrasah teachers and parents in the community. For teachers train students consciousness to fight and prevent corruption of the smallest things that is cheating, ditching and violating school rules. Parent and anti-corruption education should be taught to children from childhood, as familiarize honesty, responsibility and homely.